Design and Performance Analysis of Multi-tier Heterogeneous Network through Coverage, Throughput and Energy Efficiency - Shabbir, A.; Khan, H. R.; Ali, S. A.; Rizvi, S. (Engineering, Technology & Applied Science Research, 2017)
The unprecedented acceleration in wireless industry strongly compels wireless operators to increase their data network throughput, capacity and coverage on emergent basis. In upcoming 5G heterogeneous networks inclusion of low power nodes (LPNs) like pico cells and femto cells for increasing network’s throughput, capacity and coverage are getting momentum. Addition of LPNs in such a massive level will eventually make a network populated in terms of base stations (BSs).The dense deployments of BSs will leads towards high operating expenditures (Op-Ex), capital expenditure (Cap-Ex) and most importantly high energy consumption in future generation networks. Recognizing theses networks issues this research work investigates data throughput and energy efficiency of 5G multi-tier heterogeneous network. The network is modeled using tools from stochastic geometry. Monte Carlo results confirmed that rational deployment of LPNs can contribute towards increased throughput along with better energy efficiency of overall network.